Exploring Models and Methods in Islamic Education Planning at MI Al-Ittihad - Suhendra, Hilmatun Solihat; Alim, Akhmad; Syafri, Ulil Amri; Mujahidin, Endin; Andiana, Nesia (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2025)
This study analyzes the model and methods of Islamic education planning at MI Al-Ittihad, Ciampea District, Bogor. The study focuses on the integration of Islamic values with modern needs, such as project-based learning and the use of digital technology. Using a descriptive-analytical qualitative approach, data was collected through interviews and documentation involving key stakeholders in the planning process. The findings indicate that MI Al-Ittihad employs a comprehensive planning model that integrates the Merdeka Curriculum, modern teaching methods, and flagship programs including Quranic recitation and memorization, exact sciences (Mathematics, Abacus, and Natural Sciences), religious program, and martial arts. This balanced approach supports the spiritual and intellectual development of students and produces academically and spiritually outstanding students. This study provides practical guidance for Islamic educational institutions aiming to align religious values with contemporary educational demands and contributes theoretically by presenting a contextual model that combines normative Islamic values with modern pedagogy.